1980
DOI: 10.1139/y80-169
|View full text |Cite
|
Sign up to set email alerts
|

Use of the common carotid artery in blood pressure measurement in rats. A possible source of error

Abstract: Comparison of blood pressures obtained by femoral and common carotid artery cannulation has shown that in the rat anaesthetized with Nembutal an increase in blood pressure occurs after neck surgery and common carotid artery cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Pang and Scott (1980) found that this method did not cause any alteration in the systolic pressure, as recorded by the tail cuff method or by femoral cannulation. The cannula in the carotid artery was connected with a Ttube to the perfusion pump and to a pressure transducer.…”
Section: Fixation and Processingmentioning
confidence: 77%
“…Pang and Scott (1980) found that this method did not cause any alteration in the systolic pressure, as recorded by the tail cuff method or by femoral cannulation. The cannula in the carotid artery was connected with a Ttube to the perfusion pump and to a pressure transducer.…”
Section: Fixation and Processingmentioning
confidence: 77%
“…1981;Scott and Pang, 1983] where no difference in BP was found between young SHR and WKY. In adult SHR and WKY, cannulation of one carotid artery for direct BP measure ment always caused an increase in pressure by 25-35 mm Hg [Folkowet al, 1970;Leeet al, 1983a], In Wistar rats, similar BP change due to carotid cannulation was not present when femoral cannulation was used under ether anaesthesia [Pang and Scott, 1980], It is possible that baroreceptor reflex in response to carotid cannulation is more sensitive in neonatal SHR than WKY.…”
Section: Discussionmentioning
confidence: 99%
“…The catheter was inserted into the left common carotid artery with the tip in the aortic arch, and the telemetric transmitter probe was positioned subcutaneously on the right flank (6). This procedure was preferred to aortic catheterization to minimize the surgical procedure and then facilitate the recovery process, although it suppressed the left internal carotid discharges, which may, at least temporarily [ϳ1 wk in rats (26)], influence the baroreflex function. To reduce any infection and pain, the mice received one dose (20 mg/kg ip) of amoxicillin (Clamoxyl; SmithKlineBeecham, Nanterre, France) and one dose (5 mg/kg ip) of ketoprofen (Profenid; Aventis, Paris, France).…”
Section: Surgerymentioning
confidence: 99%